Effects of foaming agent types and ratio with red flesh pitaya puree on physicochemical properties of foam-mat dried powder (Journal of Tropical Resources and Sustainable Science (JTRSS), 2024)
Red flesh pitaya (Hylocereus sp.) is a highly perishable fruit with a high content of bioactive compound. It has short shelf life due to high moisture content and water activity. In this study, red flesh pitaya (RFP) powder was produced via foam mat drying method (FMD) with egg albumen (EA) and whey protein isolate (WPI) as the foaming agents. This study aimed to investigate the effect of foaming agent types and its ratio with RFP puree on physicochemical properties of foam-mat dried RFP powder. RFP fruit was incorporated and foamed with EA and WPI at 0 %, 5 %, 15 % and 30 % w/w concentrations. The foam was dried at 65 ?C for 5 hours. The powders were analysed for its moisture content, water activity, solubility, density, colour, fiber and total soluble solid (TSS). Decreasing the puree concentration from 85% to 55% while increasing the concentration of foaming agents (0% to 30%) has decreased the value of moisture content, water activity, crude fiber and colour properties. Meanwhile, the solubility, density and TSS of the foam-mat dried RFP powder was increased with increasing the concentration of both foaming agents (decreasing the ratio of RFP puree) used. The quality of powder foamed with WPI has produced the lowest in moisture content (2.86 %) and water activity (0.18), high in solubility (71.03 %), densities (0.56 g/cm3 and 0.84 g/cm3) and high in TSS (9.61). Meanwhile, the quality of samples foamed with 5% EA and 80% of RDF puree observed high in fiber content (3.38 %) and mostly retains the colour properties. FMD technique may be applied as the preservation technique of fruit powder as it has produced the powder with low moisture content and good colour properties within a short time and is more economical.
Keywords: foam mat; drying; red pitaya; powder; fiber